Innovative marketing: the nature and features (Journal of Economic Research & Business Administration, 2015)
"The article deals with the concept, the role of innovative marketing to increase the competitiveness of the country. The author has proposed recommendations for the support of innovative marketing in the Republic of Kazakhstan."
Keywords: Industrial and innovative projects